How prepared are trainee teachers of University Putra Malaysia (UPM) to integrate computer technology in classroom teaching? - Mohamed, Shamsiah; Bakar, Ab. Rahim (Science Publications, 2008)
This research is a presentation of a study on trainee teachers' preparedness to integrate computer technology in teaching. One-hundred and thirty-nine trainee teachers participated in the study. They comprised 12.2% male students and 87.8% female. They majored in agricultural science, home-science, language, economics or accounting and science and mathematics. Their academic achievements were between 2.00 and 3.74 (Mean = 2.91, SD = 0.41). More than 50% of them felt ready to integrate computer in teaching. In general, UPM trainee teachers had positive attitudes towards the integration of computer in teaching. They had a moderately high computer efficacy. There are significant relationships between attitudes towards the integration of computers in teaching and their perceptions about their abilities to work on: data base graphics, electronic spreadsheet and word processing.